NAD+ metabolism enzyme NNMT in cancer-associated fibroblasts drives tumor progression and resistance to immunotherapy by modulating macrophages in urothelial bladder cancer - Jian Huang; Bo Wang; Dong Yan; Tianxin Lin; Lu Pei; Hao Yu; Wang He; Kaiwen Li; Meihua Yang; Weibin Hou; Honghui Zeng; Xin-Ke Zhang; et al. (Journal for ImmunoTherapy of Cancer)
Background This study comprehensively investigates the association between the expression of nicotinamide N-methyltransferase (NNMT) and clinical outcomes of urothelial bladder cancer (UBC), as well as the molecular mechanisms by which NNMT in cancer-associated fibroblast (CAF) modulates tumor progression and immunotherapy resistance in UBC.Methods Single-cell transcriptomic analyses, immunohistochemical and immunofluorescence assays were performed on bladder cancer samples to validate the relationship between NNMT expression and clinical outcomes. A series of experiments, including chromatin immunoprecipitation assay, liquid chromatography tandem mass spectrometry assay, and CRISPR‒Cas9 (Clustered Regularly Interspaced Short Palindromic Repeats and CRISPR-associated protein 9) knockout, together with in vivo models, have been established to determine the molecular functions of NNMT in CAFs in UBC.Results We demonstrated that elevated expression of the nicotinamide adenine dinucleotide (NAD+) metabolism enzyme NNMT in CAFs (NNMT+ CAFs) was significantly associated with non-response to programmed death-ligand 1 (PD-L1) blockade immunotherapy in patients with UBC and predicted the unfavorable prognosis of UBC in two independent large cohorts. Targeting NNMT using the inhibitor 5-Amino-1-methylquinolinium iodide significantly reduced tumor growth and enhanced the apoptotic effects of the anti-PD-L1 antibody in UBC mouse models. Mechanistically, NNMT+ CAFs recruit tumor-associated macrophages via epigenetic reprogramming of serum amyloid A (SAA) to drive tumor cell proliferation and confer resistance to programmed death-1/PD-L1 blockade immunotherapy.Conclusions NNMT+ CAFs were significantly associated with non-response to PD-L1 blockade immunotherapy in patients with UBC. Elevated NNMT, specifically in CAFs, upregulates SAA expression and enhances the recruitment and differentiation of macrophages in the tumor microenvironment, thereby directly or indirectly promoting tumor progression and conferring resistance to immunotherapies in bladder cancer.